Pelatihan dan Pengembangan Keterampilan Masyarakat dalam Memanfaatkan Lahan Pekarangan Melalui Budidaya Tanaman Cabai - Tommi Tommi; Irja Tobawan Simbiak; Marshal Arung Lamba; Juliani Wairata; Sudiro Sudiro; Lazarus Ramandei (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Kampung Mosso is one of the villages located in the Jayapura city government area and is a border area between the Republic of Indonesia and Papua New Guinea. The purpose of this community service activity is to improve the community's ability to utilize their yard land by cultivating chili plants. The Community Service Activity was carried out in July 2024. The training was attended by more than 40 participants who were members of the Mosso Village community. Participants consisted of village officials, community leaders, school principals, church administrators, and the general public. The results obtained from this training are that some people have started to be able to cultivate chili plants. However, some people still cannot, this can be seen from some seeds that do not grow.